A long-term study on crustacean plankton of a shallow tropical lake: the role of invertebrate predation - Arcifa, Marlene S.; Santos Ferreira, Tania C. dos; Fileto, Claudia; Maioli Castilho-Noll, Maria S. [UNESP]; Bunioto, Tais C.; Minto, Walter J. (Pagepress Publ, 2015)
The primary factor that governs the size and species composition of zooplankton is still a controversial issue and temperature is considered the main factor responsible for latitudinal differences. In waters with a narrow temperature range, such as in the tropics, predation may be a more important factor. Nearly three decades of intermittent studies of the crustacean plankton in a shallow tropical lake revealed that the main event that led to their restructuring was the appearance of a second predator, the water mite Krendowskia sp. The new predator and larvae of the dipteran Chaoborus brasiliensis Theobald exerted a combined, although asymmetrical effect on microcrustaceans. The period when the mite was detected was followed by the restructuring of the crustacean plankton community. Predation by these two invertebrates emerged as the factor responsible for community changes, involving an increased contribution of copepods and decreases in the relative abundance of smaller cladoceran species. In the short term, the mite caused a decrease in species richness and the annual mean instantaneous composition of cladocerans, a predominance of large-sized species (Daphnia ambigua Scourfield and Daphnia gessneri Herbst) and the virtual disappearance of small species (e. g., Bosmina tubicen Brehm). The long-term impact resulted in increased species richness and the dominance of large and medium-sized cladocerans, such as D. gessneri and Ceriodaphnia richardi Sars. The larger body size of three cladocerans, the two Daphnia species and B. tubicen, in the long term, may be a response to the dominant predator, Chaoborus. The seasonal variation in the predator abundance, mainly Chaoborus larvae, allowed the prey to recover during the cool season. The copepods Tropocyclops prasinus meridionalis (Fischer) and Thermocyclops decipiens Kiefer were less affected by predation than the cladocerans; their contribution to the crustacean plankton increased 12-28% after the mite appeared. The top-down effect on crustacean plankton did not affect the phytoplankton, which remained dominated by chlorophyceans and the nanoplankton fraction before and after the zooplankton community restructuring.
Keywords: Copepods; cladocerans; chaoborid; water mite; species and size composition